Gadget Addiction Pada Anak Di KB Nurul Ulum Desa Gondanglegi Kecamatan Prambon Kabupaten Nganjuk - Risnasari, Norma; Herawati, Elysabet; Mawadha, Sarah Azmillaely; Rahayu, Fina; Purnamaningtyas, Bella Ananti (Jurnal ABDINUS : Jurnal Pengabdian Nusantara, 2020)
Gadget addiction is a form of over dependency on cellphone usage. Increasing the number of gadget addictions, children will be at risk of impaired concentration and hyperactivity because gadget addiction affects excessive release of the hormone dopamine. Besides that, children under 5 years old tend to be less sociable and lazy to do activities. They will choose to play gadgets rather than playing outside the home with peers. The aims of this counseling is expected to guardians of students know and understand about gadget addiction in children. The method used in the form of lectures and questions and answers. Based on the results of the pre-test, 8 participants (13,8%) said they did not know about the definition, 5 participants (8,6%) said they did not know the cause, 16 participants (27,6%) did not know the characteristics and 24 participants (41,4%) do not yet know how about to prevent children who are addicted to gadgets. The post-test results, 58 participants (100%) said they knew about the definition, 52 participants (91,4%) said they knew the causes, characteristics and efforts to prevent children who experience addiction to gadgets. therefore, it is expected that parents can prevent and overcome gadget addiction in children by directing the use of these gadgets for positive activities and the assistance of parents.